The level of student’s pride in Ruteng (East Nusa Tenggara) high school on Bahasa - Ifran Nurtriputra; Heppy Atma Pratiwi (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The younger generation of Indonesia unconsciously affected and following everydevelopment of communication technology that many use a foreign language. The changes oflanguage attitude of the students is inseparable from the literary situation in Indonesia. Indonesiasociety generally are bilingual and multilingual. In the literary situation like that there will be alanguage change in behavior that may not support the existence of one of the languages. From theperspective of sociolinguistics, the phenomenon of language attitude can determine the survival ofthe language. The object in this research is SMA 1 (1 High School) Ruteng, Nusa Tenggara Timur(NTT). The benefits of this research are able to be guidelines for the community's evocative,especially the young generation in addressing our national language with more pride, because thelanguage is one of the nation's identity. The results of this research show that 57, 58% feel proud touse the language of Indonesia, 42.42% regarded English is more attractive than in Bahasa. Studentswho support Bahasa became the international language of 29 respondents (87, 88%). Therespondents have thought optimistic Bahasa can exist in an era of globalization only 23 ofrespondents (69, 70%) while 10 respondents (30, 30%) were still skeptical that Bahasa became theinternational language.